The TargetMine Data Warehouse: Enhancement and Updates - Chen, Yi-An; Tripathi, Lokesh P.; Fujiwara, Takeshi; Kameyama, Tatsuya; Itoh, Mari N.; Mizuguchi, Kenji (Frontiers in Genetics, 2019)
Biological data analysis is the key to new discoveries in disease biology and drug discovery. The rapid proliferation of high-throughput “omics” data has necessitated a need for tools and platforms that allow the researchers to combine and analyse different types of biological data and obtain biologically relevant knowledge. We had previously developed TargetMine, an integrative data analysis platform for target prioritisation and broad-based biological knowledge discovery. Here we describe the newly modelled biological datatypes and the enhanced visual and analytical features of TargetMine. These enhancements have included: an enhanced coverage of gene-gene relations, small molecule metabolite to pathway mappings, an improved literature survey feature, and in silico prediction of gene functional associations such as protein-protein interactions and global gene co-expression. We have also described two usage examples on trans-omics data analysis and extraction of gene-disease associations using MeSH term descriptors. These examples have demonstrated how the newer enhancements in TargetMine have contributed to a more expansive coverage of the biological data space and can help interpret genotype-phenotype relations. TargetMine with its auxiliary toolkit is available at https://targetmine.mizuguchilab.org. The TargetMine source code is available at https://github.com/chenyian-nibio/targetmine-gradle.